Local’s Participation in Evolving Gastronomy Tourism in Ubud and Beyond - Wulandari, Pande Putu; Tirtawati, Ni Made (Institut Pariwisata Trisakti, 2023)
The Ministry of Tourism has chosen Ubud to represent the UNWTO gastronomy destination prototype. The locals' involvement in creating an inclusive gastronomy destination deserves consideration because they have a significant stake and direct role in integrating its culinary characteristics to create a distinctive gastronomy destination. By evaluating the local's readiness and identifying the potential of its gastronomic features, this study seeks to investigate the locals' participation in developing gastronomic tourism in Ubud and beyond. Through interviews with key informants, such as local leaders, governments, organizations, and associated practitioners, and observations, this research determines the level of locals' participation by evaluating their readiness. In addition, interviews with local's representatives at 13 tourism villages in Ubud and beyond, who are members of BUMDes Bersama Gianyar Aman, were also conducted. Data analysis was performed through the Community Readiness Model approach and analyzed using qualitative descriptive analysis techniques. The results showed that the local readiness level is at the fourth stage. Even though it is still in the pre-planning stages, the locals are prepared to develop gastronomy tourism. The leadership dimension is primarily influencing the level of local's readiness. Meanwhile, the dimension of community efforts needs to be improved in responding to local's readiness by increasing involvement in various efforts. Keywords: Gastronomy Destination, Local’s Participation, Community Readiness Model, Tourism Village; Ubud.